Use of IMMPACT Recommendations to Explore Pain Phenotypes in People with Knee Osteoarthritis. Issue 10 (10th March 2022) - Carlesso, Lisa C; Feldman, Debbie Ehrmann; Vendittoli, Pascal-André; LaVoie, Frédéric; Choinière, Manon; Bolduc, Marie-Ève; Fernandes, Julio; Newman, Nicholas; Sabouret, Pierre
Abstract: Objective: Knee osteoarthritis (OA) is a disease of multiple phenotypes of which a chronic pain phenotype (PP) is known. Previous PP studies have focused on one domain of pain and included heterogenous variables. We sought to identify multidimensional PPs using the IMMPACT recommendations and their relationship to clinical outcomes. Methods: Participants >40 years of age with knee OA having a first-time orthopedic consultation at five university affiliated hospitals in Montreal, Quebec, and Hamilton (Canada) were recruited. Latent profile analysis was used to determine PPs (classes) using variables recommended by IMMPACT. This included pain variability, intensity and qualities, somatization, anxiodepressive symptoms, sleep, fatigue, pain catastrophizing, neuropathic pain, and quantitative sensory tests. We used MANOVA and χ 2 tests to assess differences in participant characteristics across the classes and linear and Poisson regression to evaluate the association of classes to outcomes of physical performance tests, self-reported function and provincial healthcare data. Results: In total, 343 participants were included (mean age 64 years, 64% female). Three classes were identified with increasing pain burden (class3 > class1), characterized by significant differences across most self-report measures and temporal summation, and differed in terms of female sex, younger age, lower optimism and pain self-efficacy. Participants in class2 and class3 had significantly worse self-reported function, stair climb and 40 m walk tests, and higher rates of healthcare usage compared to those in class1. Conclusions: Three distinct PPs guided by IMMPACT recommendations were identified, predominated by self-report measures and temporal summation. Using this standardized approach may improve PP study variability and comparison.